-2(5s-5)-10=-2(9s+4)-2

Simple and best practice solution for -2(5s-5)-10=-2(9s+4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5s-5)-10=-2(9s+4)-2 equation:


Simplifying
-2(5s + -5) + -10 = -2(9s + 4) + -2

Reorder the terms:
-2(-5 + 5s) + -10 = -2(9s + 4) + -2
(-5 * -2 + 5s * -2) + -10 = -2(9s + 4) + -2
(10 + -10s) + -10 = -2(9s + 4) + -2

Reorder the terms:
10 + -10 + -10s = -2(9s + 4) + -2

Combine like terms: 10 + -10 = 0
0 + -10s = -2(9s + 4) + -2
-10s = -2(9s + 4) + -2

Reorder the terms:
-10s = -2(4 + 9s) + -2
-10s = (4 * -2 + 9s * -2) + -2
-10s = (-8 + -18s) + -2

Reorder the terms:
-10s = -8 + -2 + -18s

Combine like terms: -8 + -2 = -10
-10s = -10 + -18s

Solving
-10s = -10 + -18s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '18s' to each side of the equation.
-10s + 18s = -10 + -18s + 18s

Combine like terms: -10s + 18s = 8s
8s = -10 + -18s + 18s

Combine like terms: -18s + 18s = 0
8s = -10 + 0
8s = -10

Divide each side by '8'.
s = -1.25

Simplifying
s = -1.25

See similar equations:

| 8y-3=14y+15 | | X+10/5+4/5x | | 8x+21=7x-6 | | 8y-3=14+15 | | 16x^2-32=0 | | (4+2x)2=2+-2x | | h/3+9=13 | | 48(2x-1)=8(x+4)+3x | | 4(5+2v)=84 | | 10x^2-5x-25=0 | | m(m+5)=-4 | | 1/2(7-3(6+1)) | | 9x-(5x+11)=25 | | -2(4s-1)-2=-3(9s+3)-5 | | -5x=300 | | (2x+5)(2x+5)=27 | | y-13/5=16/5 | | 11-0.10x=10 | | 4a^2=16a | | 27-3x=15 | | 4/21x7/12 | | 4w^2+16+7=0 | | 9(2-j)+3(5+2j)=2(7-2j)-4(4j-1) | | 4/21*7/12 | | (w)(2w-1)=91 | | (w)(2w^2)=91 | | 8v^2+10v-3=0 | | x/20-5=-4 | | -4(-5-3x)=116 | | 25x^2+30=55 | | B-24.6=5.1b | | 2+x/4=-2 |

Equations solver categories